2009
DOI: 10.1002/pro.236
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Cdt1 C‐terminal domain: Conservation of the winged helix fold in replication licensing factors

Abstract: In eukaryotic replication licensing, Cdt1 plays a key role by recruiting the MCM2-7 complex onto the origin of chromosome. The C-terminal domain of mouse Cdt1 (mCdt1C), the most conserved region in Cdt1, is essential for licensing and directly interacts with the MCM2-7 complex. We have determined the structures of mCdt1CS (mCdt1C_small; residues 452 to 557) and mCdt1CL (mCdt1C_large; residues 420 to 557) using X-ray crystallography and solution NMR spectroscopy, respectively. While the N-terminal 31 residues o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 54 publications
5
42
0
2
Order By: Relevance
“…5C and data not shown). Four of the five phosphorylation sites (S391, T402, T406, and S411) lie in a flexible region of Cdt1 (36,39) that is sufficient for Mcm6 binding in vitro (70). Cdt1 is a highly dynamic protein both in vivo (72) and in a reconstituted MCM loading assay using purified Saccharomyces cerevisiae proteins (56) consistent with a model in which Cdt1 rapidly shuttles between the nucleoplasm and an origin-bound ORC-Cdc6 loading machine.…”
Section: Discussionmentioning
confidence: 61%
“…5C and data not shown). Four of the five phosphorylation sites (S391, T402, T406, and S411) lie in a flexible region of Cdt1 (36,39) that is sufficient for Mcm6 binding in vitro (70). Cdt1 is a highly dynamic protein both in vivo (72) and in a reconstituted MCM loading assay using purified Saccharomyces cerevisiae proteins (56) consistent with a model in which Cdt1 rapidly shuttles between the nucleoplasm and an origin-bound ORC-Cdc6 loading machine.…”
Section: Discussionmentioning
confidence: 61%
“…Though the C terminus of Cdt1 binds to MCM2-7, the essential N terminus of Cdt1 has been shown to be critical for loading MCM2-7, along with Cdc45 and GINS, which stimulate helicase activity (51). The recent solution structure of the C-terminal domain of Cdt1 (aa 450 to 557 and aa 420 to 557 of mouse Cdt1) by X-ray crystallography and nuclear magnetic resonance (NMR) revealed the presence of a winged-helix domain that could possibly interact with MCM (23,24). Similarly, NMR studies have revealed the interaction between human Cdt1 (aa 410 to 440) and MCM6 (aa 708 to 821) (29).…”
Section: Discussionmentioning
confidence: 99%
“…Addendum-While we were in preparation of the manuscript, a report describing the solution and crystal structures of C-terminal regions of mouse Cdt1 was published (55).…”
Section: Acknowledgments-we Thank Drs Toshihiko Eki For Constructingmentioning
confidence: 99%